Implementation of a Bullying and Violence Prevention Application as a Reinforcement of a Child-Friendly School at SMP PGRI 1 Semarang: Implementasi Aplikasi Pencegahan Bullying dan Kekerasan sebagai Penguat Sekolah Ramah Anak di SMP PGRI 1 Semarang - Senowarsito, Senowarsito; Werdiningsih, Yuli Kurniati; Herlambang, Bambang Agus; Indradewi, Marlisa (Universitas Lancang Kuning, 2024)
This community service activity aims to implement a bullying and violence prevention application in a partner school to create a Child-Friendly School (CFS). The main issue identified is the lack of shared perception and commitment among school personnel, students, and parents regarding the concept of bullying. The methods used include socialization, training, mentoring, as well as monitoring and evaluation. The results of the activity show an increase in understanding and commitment of all parties in preventing bullying, as well as the formation of a more effective prevention mechanism. The importance of these results is to build a safe and comfortable school environment for all students, and ultimately to achieve the vision of child-friendly education in Semarang City